Possibilidades de ações da gestão escolar para a inserção profissional dos professores dos anos iniciais - Moretti, Vivian Maggiorini (Universidade Federal de São Carlos, 2021)
The research has as object to evidence and analyze the possibilities of actions of the school management in the process of professional insertion of teachers declared by teachers of the initial years. For this, a qualitative approach research was carried out, which sought to make sense of the meaning and meaning of the messages, as it allows us to analyze human beings in their relationships with each other, with society and with nature, considering their complexity in the context of regulated subjects. For the construction of the data, a mapping of the beginning teachers of the municipal secretariat of Sorocaba-SP was carried out and a questionnaire with mixed questions was used to obtain an overview of the insertion of teachers in this public network. In order to deepen the data, we opted for semi-structured changes with early-career teachers selected from the questionnaire. An interpretive analysis considered as phases of the professional life cycle defined by Huberman (2000), as a result of teacher development and the process of insertion in the teaching career, which is composed of a peculiar initial professional phase due to the different working conditions, in addition to being considered a period of many learnings. The analysis used the data categorization technique, from a questionnaire and semi-structured interviews with beginning teachers and as theoretical bases on the beginning of the career and professional insertion of teachers (HUBERMAN, 2000; MARCELO GARCIA, 1999 and 2009; MIZUKAMI, 2000 ; TARDIF, 2014) and on school management (LIBÂNEO, 2012; PARO, 2005). Two axes were identified that show the insertion process and the contributions of managers in this early stage of their career, as well as their valuation. The first axis consisted of two categories to analyze the inclusion of teachers in the initial years surveyed. The second axis was composed of three analytical categories of possibilities for actions in school management: reception and reception, monitoring and training. The main results show that, for beginning teachers, the actions and good practices of the management team, offered to the teacher during insertion, ensure greater security in their work, even in the face of difficulties encountered in the beginning of their career.
Possibilities of school management actions for the professional insertion of teachers in the early years
Keywords: inserção Profissional; Professor Iniciante; Gestão Escolar; Professional Insertion; Beginning Teacher; School Management; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM